2009
DOI: 10.1542/peds.2008-3346
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavior in Term, Small-for-Gestational Age Infants With Normal Placental Function

Abstract: Term SGA newborns with no signs of placental insufficiency had poorer neurobehavioral competencies, which suggests delayed neurologic maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 54 publications
13
99
1
3
Order By: Relevance
“…Fetuses with an expected fetal weight below 10th centile but normal Doppler in the UA are generally considered as constitutional normally small fetuses. Recent publications highlight that within this group there are some cases having an abnormal perinatal outcome [20,21]. Clearly, this is a heterogeneous group and additional fetal hemodynamic parameters should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuses with an expected fetal weight below 10th centile but normal Doppler in the UA are generally considered as constitutional normally small fetuses. Recent publications highlight that within this group there are some cases having an abnormal perinatal outcome [20,21]. Clearly, this is a heterogeneous group and additional fetal hemodynamic parameters should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A deficient state organization and regulation was found in SGA newborns, suggesting a delay in neurological maturation) (Figueras et al, 2009). However, this discrepancy must be qualified, because significant differences have been found in two items (Response Decrement Light and General Tone), confirming the worse performance of SGA newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed LBW but neglected the GA or indistinctly used LBW and prematurity (Davis et al, 2007;Ohgi et al, 2003). Other research has demonstrated that the LBW, per se, taken separately from prematurity, is also a risk factor and has highlighted that SGA full term babies perform worse in neurobehavioral tests than neonates of an adequate birthweight (Costas-Moragas, 2009;Figueras et al, 2009).…”
Section: *) Introductionmentioning
confidence: 99%
“…Sanz-Cortes et al (2010) [9] FGR fetuses with normal umbilical PI matched with AGA controls were studied by functional MRI at 37 weeks to measure markers of brain microstructure and metabolism. [67] Evaluation of neurobehavioral outcomes of term FGR with normal UmA-PI.…”
Section: Middle Cerebral Arterymentioning
confidence: 99%
“…In addition, in a subset of other late FGR environmental factors might play a major role in determining growth restriction, such as heavy maternal smoking [66], poor maternal nutrition [13], and others. Thorough consideration of these diagnostic criteria could be helpful in proper definition of FGR versus SGA, important differentiation as supported by the analysis of perinatal outcomes [67,68]. In the longitudinal post-natal studies by Figueras et al, SGA was defined based on the inclusion criteria.…”
Section: Late Onset and Term Fetal Growth Restrictionmentioning
confidence: 99%